A comparison forecasting models for ASEAN equity markets - Wong, Yoke Chen *; Kok, Kim Lian (Sunway University College, 2005)
This paper compares six models for forecasting the performance of the ASEAN equity markets of Malaysia, Singapore, Thailand, Indonesia and the Philippines before, during and after the Asian financial crisis. In the precrisis period, the OLS, ARCH-M and TARCH models have better forecasting performance than the other models. In the crisis period, the ARCH-M model has the best forecast performance for three markets, while the remaining two markets are best forecast with the random walk model. However, in the post-crisis period, the TARCH and EGARCH models are found to be the most suitable models. The different variants of the GARCH model adequately captured the time-varying returns volatility. But the asymmetry of the market returns is not significant in all the markets modelled by the TARCH and EGARCH models.